Rare case of hereditary spherocytosis with rheumatic mitral stenosis - Mathur, Alok; Gupta, Jugal Bihari; Joad, Mohammad Izhar; Ravte, VedaShree; Jain, Priyansha; Brar, Ajit Singh (Indian Journal of Case Reports, 2024)
A rare case of hereditary spherocytosis (HS) and rheumatic mitral stenosis coexisting in a patient having severe stenosis, atrial fibrillation, and symptoms of the left ventricular dysfunction, along with hemolytic anemia attributed to HS. We present the case of a 58-year-old lady who presented to the emergency department with complaints of increasing shortness of breath for the past week. She was examined to have atrial fibrillation with a fast ventricular rate. On investigations, she was found to have severe rheumatic mitral stenosis with evidence of hemolytic anemia. Further, evaluation of the cause of her anemia revealed HS. This case highlights the importance of the evaluation of anemia in patients with valvular heart diseases. If a treatable cause is found, anemia can be treated to reduce the cardiac burden.Abstract:Background-  A rare case of  Hereditary Spherocytosis and Rheumatic Mitral Stenosis coexisting in a patient having severe stenosis, atrial fibrillation and symptoms of left ventricular function, along with hemolytic anemia attributed to HS.  .Case presentation- We present a case of a 58-year-old lady presented to the Emergency Department with complaints of increasing shortness of breath in the last one week. She was examined to have Atrial Fibrillation with a Fast Ventricular Rate. Upon Investigations, she was found to have severe Rheumatic Mitral Stenosis with evidence of Hemolytic anemia. Further evaluation of the cause of her anemia revealed Hereditary Spherocytosis.  Conclusion- This case highlights the importance of evaluation of anemia inpatients with valvular heart diseases. If a treatable cause is found, anemia can be treated to reduce the cardiac burden.